Essentials of strategic management : the quest for competitive advantages - Gamble, John E.; Peteraf, Margaret A.;Thompson Jr., Arthur A. (New York : McGraw Hill Education, 2015)
Essentials of Strategic Management presents a conceptually strong treatment of strategic management principles and analytic approaches that features straight-to-the-point discussions, timely examples, and a writing style that captures the interest of students. The Fourth Edition of Essentials of Strategic Management is very much in step with the best academic thinking and contemporary management practice. The chapter content continues to be solidly main-stream and balanced, mirroring both the penetrating insight of academic thought and the pragmatism of real-world strategic management. The text serves as the theoretical foundation of a teaching approach incorporating a business strategy simulation.
Concepts and techniques for crafting and executing strategy -- Cases in crafting and executing strategy
Includes index.
Keywords: STRATEGIC PLANNING